Autour du centenaire d’Octobre 1917. Réflexions sur la transmission mémorielle, l’engagement politique et la fabrique du sujet communiste révolutionnaire à Lutte ouvrière - Benjamin Flammand (Amnis)
The concept of historical memory appears to be particularly useful to the sociology of commitment. From the perspective of transmission and the system of interactions it is based on, it allows us to question the way individual experiences are brought into line with the historical memory. Through the process of recruitment of the French Trotskyist organization « Lutte ouvrière » (considered as a case study), the concrete ways of the transmission of memory reveals, way before the formal commitment, how the revolutionary communist subject is produced.